Emil Salim [Indonesia, Minister of Environment] - Salim, Emil (Institutional Knowledge at Singapore Management University, 2014)
Emil Salim was part of the famed Berkeley Mafia who brought Indonesia out of its economic crisis in the mid-1960s. He later went on to become Minister of Environment in President Suharto's cabinet. He speaks to DNA about how he overcame obstacles in his career, even when he did have subject knowledge, and what it was like working with President Suharto.